Interactive E-Module Development on Temperature Matter for Junior class VII - Hidayah, Nurul; Firdaus, Thoha; Sinensis, Arini Rosa (Universitas Muhammadiyah Sidoarjo, 2024)
This article discusses the development of an interactive e-module on temperature-related topics for 7th-grade junior high school students, aiming to enhance their learning skills. Employing the 4D development model (Define,Design, Develop, Disseminate), the research focuses on optimizing technology's role in education, motivating students to actively engage in learning, and facilitating easy access for independent learning. The developmental process involves defining needs, designing solutions, implementing them, and disseminating the final product. The resulting e-module, accessible online, incorporates multimedia features, quizzes, and interactive elements to increase student engagement with temperature-related concepts. Expert validation indicates a high level of validity, affirming the effectiveness of the e-module as a learning tool. The conclusion emphasizes the innovative role of e-modules in enriching students' learning experiences and boosting their interest in temperature-related subjects within the school environment.